Copropriété divise et assurance : le nouveau droit - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1993)
The author presents and comments on the new articles of the Québec Civil Code governing condominiums and which are expected to come into force in 1994. The first part of the study, which we published in the July 1993 issue, deals with the general notions, the formal changes, and the main aspects of the Declaration of Co-ownership as regards insurance as well as the principles of insurance as they apply to this area. The second part, deals with the provision of insurance policies taken out either collectively by the administrators or individually by the co-owners.